'I love you more': An account of performing ziyarat in Iraq. (1st May 2015) - Shannahan, Dervla Zaynab
This article reflects on fieldwork experience of performing ziyarat in Iraq in May 2014. It offers an embodied account of ziyarat rituals and practices, and discusses re/construction. It emphasizes that existing literature on ziyarat practices in Iraq is minimal, as is recent research on the country. This article approaches ziyarat as a sociopolitical performance that may simultaneously function as an individual response to the Karbala experience. It draws on El-Aswad's exploration of 'invisible realities' and the 'different logic' of spiritual love in structuring Shia'ah ritual, and rapper Sulaiman's use of 'extreme love' in understanding Islamic history. The approach follows on from Al-Adeeb's work, and Al-Mohammad and Peluso's call for attention to how creative and spiritual practices, and everyday experiences, can enhance our understanding of the continuation of life in Iraq. Five months since this research was conducted, the conditions of life in Iraq and potential ziyarat experiences described have been changed by the security situation and ISIS. This article must therefore be read as recent research that may have already become history.